Exciting opportunities in planetary structural geology and tectonics: An early career perspective - Crane, Kelsey; Galluzzi, Valentina (Frontiers in Earth Science, 2022)
The outer shells of solid planetary bodies have been all subject to deformation during their history. The nature and style of deformation strictly depends on the evolution of each planetary body. Earth’s lithospheric style of deformation is related to plate tectonics, but it turns out to be a unique case in our Solar System. How can we study the tectonics of other planetary bodies? How and why do planetary lithospheres deform, and what are the implications of these processes? These are the driving questions for investigations of modern planetary structural geology. The improvement in technology, machine learning analyses, and quality and quantity of planetary space mission data give us the chance to deepen our grasp in planetary surface deformation. The lack of micro-to-local scale information that is so crucial in Earth structural geology studies has driven planetary structural geology to advance pioneering methods to study crustal deformation. Conversely, the study of old deformed surfaces such as those of Mercury, the Moon and Mars will deepen our grasp on the early evolution of Earth tectonics.